Firearm injuries in children: a missed opportunity for firearm safety education. Issue 6 (12th January 2021) - Stokes, Sarah C; McFadden, Nikia R; Salcedo, Edgardo S; Beres, Alana L
Abstract : Background: Surgeons frequently care for children who have sustained gunshot wounds (GSWs). However, firearm safety education is not a focus in general surgery training. We hypothesised that firearm safety discussions do not routinely take place when children present to a trauma centre with a GSW. Method: A retrospective review of patients <18 years presenting with GSWs to a level 1 paediatric trauma centre from 2009 to 2019 was performed. The primary outcome was discussion of firearm safety with the patient or family. The secondary outcome was notification of child protective services (CPS). Results: A total of 226 patients with GSWs were identified, 22% were unintentional and 63% were assault. Firearm safety discussions took place in 10 cases (4.4%). Firearm safety discussions were more likely to occur after unintentional injuries compared with other mechanisms (16.0% vs 1.3%, p<0.001). CPS was contacted in 29 cases (13%). CPS notification was more likely for unintentional injuries compared with other mechanisms (40% vs 3.9%, p<0.001) and for younger patients (7 years vs 15 years, p<0.001). Conclusion: At a paediatric trauma centre, firearm safety discussions occurred in 4.4% of cases of children presenting with a GSW. There is a significant room for improvement in providing safety education interventions.